Unveiling Current and Future Trends in the Implementation of Teaching Games for Understanding in Primary School: A Bibliometric Analysis - Irfan Oktavianus; Uray Gustian; Andika Triansyah (Physical Education Theory and Methodology)
Background. Physical Education (PE) often focuses on sports skills through command-based teaching methods, which can lead to students struggling to understand and effectively play games. To address this issue, Teaching Games for Understanding (TGfU) has been introduced as a more effective approach to enhance tactical comprehension and gameplay skills, while also increasing student engagement in physical activities.